Plexor the raging reptile - Blade, Adam (Blade, Adam. Beast quest, 2015)
"In a desert oasis a terrifying creature lies in wait. Plexor, a monstrous water Beast, is guarding the missing royal sceptre. Tom and Elenna must conquer the Beast, or all the kingdoms are doomed!"--Back cover.